RESOLUTION OF NON-PERFORMING LOANS IN CREDIT AGREEMENTS WITHOUT MORTGAGE DEED AT THE CUSTOMARY VILLAGE CREDIT INSTITUTION (LPD) OF PADONAN TIBUBENENG, NORTH KUTA, BADUNG - Dewi, Ni Kadek Marantina; Mahendrawati, Ni Luh Made; Sukandia, I Nyoman (jfpublisher, 2024)
The enactment of Law No. 4/1996 on Mortgage Rights mandates that any action establishing land rights under Law No. 5/1960 on Agrarian Principles must involve the granting of mortgage rights via APHT as debt repayment security, with the Mortgage Rights Deed being a crucial part of the debt agreement. Despite this, some financial institutions like LPD Padonan Tibubeneng Customary Village extend credit without APHT. Researchers are interested in LPD Padonan’s response to defaulted agreements, which pose a legal discrepancy. Similar cases arise in various LPDs in Bali, where credit is granted with collateral but lacks a mortgage deed, leading to legal issues upon default. LPD Padonan faces the same challenge, hindering collateral execution upon default. Empirical legal research, using legal concepts and theories, is conducted, supplemented by data from LPD Padonan. Steps taken upon default, before non-performing loan status, involve warning letters and subpoenas. If unsuccessful, credit settlement by Padonan LPD occurs through two channels: non-litigation avenues such as deliberations and credit restructuring, particularly for Padonan residents, and customary settlement through paruman.